Pengaruh Label Halal, Religiusitas, Harga, dan Review Produk Terhadap Keputusan Pembelian Produk Kecantikan Skintific Pada Kalangan Gen Z di Kabupaten Bangkalan - Alan Suud Maadi; Alfina Damayanti; Ahmad Makhtum (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The Indonesian government now requires halal certification for all products in Indonesia, including cosmetics. However, many products still do not carry the halal label, including some Skintific products. On the other hand, individual religiosity plays a more profound role because it reflects the extent to which religious values ​​are the basis for product selection. Skintific sales are very high compared to other beauty products despite its relatively high price. In this digital era, product reviews from other users also play a significant role in shaping brand perceptions and trust. The method used in this study was quantitative, with data collection using a questionnaire. The results of this study indicate that the halal label does not significantly influence purchasing decisions, religiosity does not significantly influence purchasing decisions, price does significantly influence purchasing decisions, and product reviews significantly influence purchasing decisions. The halal label, religiosity, price, and product reviews collectively have a significant influence on purchasing decisions. The magnitude of the influence of the halal label, religiosity, price, and product reviews is 63.6%, influencing purchasing decisions for Skintific products among Gen Z in Bangkalan Regency. Meanwhile, the remaining 36.4% is influenced by other factors outside the model.